Nutritional Compositions in the Muscle of Yellow Puffer Fish, Xenopterus naritus (Richardson, 1848) from Kg. Manggut and Kabong, Sarawak, Malaysia - Mohd Nor Azman, Ayub; Samsur, Mohamad; Mohammed, Mohidin; Fisal, Ahmad; Fasihuddin, Badruddin Ahmad (Fisheries Research Institute, Department of Fisheries Malaysia, 2018)
This study is to report the proximate compositions in the muscles of yellow puffer fish, Xenopterus naritus which was collected from Kg. Manggut and Kabong, Sarawak between February and July 2013. The internal organs of 20 specimens of X. naritus from Kg. Manggut and Kabong, respectively were removed by local residence that possess skills and experiences with the preparation of yellow puffer fish. In general, the moisture contents were ranging between 75.2% and 80.6%. In the present study, X. naritus from Kabong showed higher crude protein contents (88.2% dry weight) than the same species from Kg. Manggut (87.9% dry weight) but not significantly different (p>0.05). However, X. naritus from Kg. Manggut demonstrated a significantly higher (p<0.05) of crude fat contents (0.49% dry weight), crude fibre contents (0.44% dry weight) and ash contents (5.48% dry weight) compared to X. naritus from Kabong which were 0.47%, 0.25% and 5.08% dry weight, respectively. This study shows that the yellow puffer fish could be considered as an alternative source of protein for human consumption. Further, this is the first report on nutritional compositions in edible yellow puffer fish from Sarawak.